2017
DOI: 10.1002/ccr3.902
|View full text |Cite
|
Sign up to set email alerts
|

First reported case of Simpson–Golabi–Behmel syndrome in a female fetus diagnosed prenatally with chromosomal microarray

Abstract: Key Clinical MessageSimpson–Golabi–Behmel syndrome (SGBS) is a rare X‐linked syndrome. Female carriers may have mild manifestations. Macrosomia, polyhydramnios, and kidney and urinary tract anomalies are common findings in male fetuses. We present the first case of a severely affected female fetus with stigmata of SGBS and a deletion involving the GPC3 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Table details GPC3 mutations published between March 1996 and December 2017 in the international peer‐reviewed literature (PubMed database) and The Human Gene Mutation Database (HGMD professional 2016.4) following HGVS nomenclature guidelines (http://www.HGVS.org) and the reference sequence GenBank entry NM_004484.3. We collected 57 distinct GPC3 mutations detected in 71 unrelated families (Agatep et al., ; Das Bhowmik & Dalal, ; Day & Fryer, ; DiMaio, Yang, Mahoney, McGrath, & Li, ; Ganesamoorthy et al., ; Garavelli et al., ; Gertsch, Kirmani, Ackerman, & Babovic‐Vuksanovic, ; Gurrieri et al., ; Halayem et al., ; Hughes‐Benzie et al., ; Kehrer et al., ; Kosaki et al., ; Li et al., ; Lindsay et al., ; Magini et al., ; Mariani et al., ; Mateos et al., ; Mujezinović et al., ; Ochiai et al., ; Okamoto, Yagi, Imura, & Wada, ; Pilia et al., ; Rodríguez‐Criado et al., ; Romanelli et al., ; Sakazume et al., ; Schmidt, Hollstein, Kaiser, & Gillessen‐Kaesbach, ; Shimojima et al., ; Spencer, Fieggen, Vorster, & Beighton, ; Støve et al., ; Thomas et al., ; Vaisfeld, Pomponi, Pietrobono, Tabolacci, & Neri, ; Veugelers et al., , ; Villarreal et al., ; Weichert et al., ; Xuan, Hughes‐Benzie, & MacKenzie, ; Yano et al., ; Young, Wishnow, & Nigro, ). In this study, we also report 38 GPC3 mutations in 63 additional male patients from 49 unrelated families (Cf.…”
Section: Mutational Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…Table details GPC3 mutations published between March 1996 and December 2017 in the international peer‐reviewed literature (PubMed database) and The Human Gene Mutation Database (HGMD professional 2016.4) following HGVS nomenclature guidelines (http://www.HGVS.org) and the reference sequence GenBank entry NM_004484.3. We collected 57 distinct GPC3 mutations detected in 71 unrelated families (Agatep et al., ; Das Bhowmik & Dalal, ; Day & Fryer, ; DiMaio, Yang, Mahoney, McGrath, & Li, ; Ganesamoorthy et al., ; Garavelli et al., ; Gertsch, Kirmani, Ackerman, & Babovic‐Vuksanovic, ; Gurrieri et al., ; Halayem et al., ; Hughes‐Benzie et al., ; Kehrer et al., ; Kosaki et al., ; Li et al., ; Lindsay et al., ; Magini et al., ; Mariani et al., ; Mateos et al., ; Mujezinović et al., ; Ochiai et al., ; Okamoto, Yagi, Imura, & Wada, ; Pilia et al., ; Rodríguez‐Criado et al., ; Romanelli et al., ; Sakazume et al., ; Schmidt, Hollstein, Kaiser, & Gillessen‐Kaesbach, ; Shimojima et al., ; Spencer, Fieggen, Vorster, & Beighton, ; Støve et al., ; Thomas et al., ; Vaisfeld, Pomponi, Pietrobono, Tabolacci, & Neri, ; Veugelers et al., , ; Villarreal et al., ; Weichert et al., ; Xuan, Hughes‐Benzie, & MacKenzie, ; Yano et al., ; Young, Wishnow, & Nigro, ). In this study, we also report 38 GPC3 mutations in 63 additional male patients from 49 unrelated families (Cf.…”
Section: Mutational Spectrummentioning
confidence: 99%
“…Recently, array‐CGH also allowed the detection of GPC3 rearrangements (Cf. Table ) in eight cases of prenatal diagnosis (DiMaio et al., ; Ganesamoorthy et al., ; Magini et al., ; Støve et al., ; Vuillaume et al., ; Weichert et al., ) and, in three postnatal cases of SGBS (Schmidt et al., ; Shimojima et al., ). In our cohort, chromosomal microarray was performed, after PCR, in order to fine‐map rearrangement breakpoints when they occurred at the 5′ and/or 3′end of GPC3 (Cf Table ).…”
Section: Mutational Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported certain features on prenatal ultrasound that can facilitate SGB syndrome diagnosis before birth [Chen et al, 1993;Yamashita et al, 1995;Enns et al, 1998;Weichert et al, 2011;Garavelli et al, 2012;Cottereau et al, 2013;Kehrer et al, 2016;Magini et al, 2016;Mujezinović et al, 2016;Støve et al, 2017;Zimmermann and Stanek, 2017]. Table 1 summarizes the described prenatal findings from previously published cases and our cases.…”
Section: Discussionmentioning
confidence: 91%
“…[13] Different mutations have been described in SGBS type one. [14][15][16][17][18][19][20][21][22] Overgrowth Syndrome caused by mutations in glypican 3 (GPC3) gene is localized on Xq26.1 [23,24] which encrypts glypican-3. [17,19,20,[25][26][27][28][29] that seemingly acting a bad part in growth control by an anonymous fate, However, outcomes from an exhaustive qualified study of growth forms in dual mutants missing GPC3 provided conclusive genetic evidence inconsistent with the theory that GPC3 performances as a growth suppressor.…”
Section: Introductionmentioning
confidence: 99%